AFLPs and morphological diversity of Phaseolus lunatus L. in Cuban home gardens : Approaches to recovering the lost ex situ collection - Castineiras Alfonso, L; Guzmán, F.A.; Duque E., Myriam Cristina; Shagarodsky, T; Cristobal, R; Vicente, M. Carmen de (Springer, 2007)
The genetic diversity of 76 accessions of lima bean (Phaseolus lunatus L.), collected mostly from home gardens, was assessed with AFLPs and seed descriptors to evaluate the potential for recovering a lost ex situ collection in Cuba. The sample contained 60 accessions collected from 25 home gardens in the three main geographical regions of Cuba and represented the three cultivated types found on the island. Four more accessions were part of the former ex situ collection and the remaining 12 accessions were selected from the world bean collection held at the International Center for Tropical Agriculture. Some morphological measurements discriminated among cultivated types. The analysis of 62 polymorphic bands obtained with two AFLP primer combinations indicated that the three cultivated bean types were comparable in terms of molecular diversity and that no pattern of variation was associated with geographical distribution. However, a multiple correspondence analysis with the same molecular data detected different genetic groups. Three of these groups included all the cultivated accessions collected from home gardens, but could not be explained by the seed descriptors. The results therefore suggest that a scientifically sound collecting strategy to recover the former Cuban ex situ gene bank should consider combining geographical, morphological, and molecular data. The findings also suggest that any proposed methodologies should be considered before developing a conservation strategy based on an ex situ or combined ex situ and in situ approaches.